ANALISIS KESULITAN SISWA DALAM PENYELESAIAN SOAL FISIKA GERAK HARMONIK SEDERHANA KELAS X MAN 1 PEKANBARU - Priyanti, Eka; Azhar, Azhar; Zulhelmi, Zulhelmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this study is to describe the difficulties of students of class X MAN 1 Pekanbaru in solving the physics problem of simple harmonic motion. The research started from April 2017 until June 2017. This research type is survey research with quantitative approach. The sample of this study was taken from all the existing population of students MAN 1 Pekanbaru in class X MIA, amounting to 57 people. The research instrument consists of essay test which consists of 10 questions. Data analysis technique used is descriptive analysis. The results showed that the lowest percentage of ability at 30.16% indicator determines the speed of simple harmonic motion with difficulty level